Raman spectroscopy potentiality in the study of geopolymers reaction degree. (5th June 2021) - Caggiani, Maria Cristina; Coccato, Alessia; Barone, Germana; Finocchiaro, Claudio; Fugazzotto, Maura; Lanzafame, Gabriele; Occhipinti, Roberta; Stroscio, Antonio; Mazzoleni, Paolo
Abstract: Alkali‐activated materials (AAMs) and "geopolymers" are inorganic polymeric materials obtained by mixing of solid aluminosilicate precursors with an alkaline solution (generally, KOH or NaOH and Na2 SiO3 mixed in various ratios). This class of aluminosilicate materials has emerged as a greener alternative to traditional concrete, for large‐scale as well as for niche applications such as conservation and restoration of built heritage. In this work we apply Raman spectroscopy both to aluminosilicate precursors (metakaolin, pumice, volcanic ash, volcanic soils, clayey sediments, ceramic waste) and to the respective AAMs. In the field of vibrational spectroscopy, Raman is much less employed in the literature with respect to Fourier transform infrared (FTIR) to have insights into the alkali activation process from a molecular point of view. The aim of this paper is to investigate the potentiality of a Raman approach to the comparison of the employed raw materials with the respective AAMs. Raman analyses during the first hours of geopolymerization were also carried out on the clayey sediments and ceramic waste‐based products. The results, differentiated according to the employed precursors, exhibit spectra relative to crystalline and amorphous phases that can give an indication about the newly formed aluminosilicate gel. Abstract : The potentiality of Raman spectroscopy application to the comparison of precursors with respective alkali‐activated materials was investigated. Metakaolin, pumice, volcanic ash, volcanic soils, clay, and ceramic waste were analyzed before and after—and, in some cases, during—the geopolymerization process. The resulting Raman spectra are relative to crystalline and amorphous phases that can give an indication about the newly formed aluminosilicate gel.